An analysis on the role of women in the land reform and resettlement programme in Zimbabwe. - Mashanda, Edward Tinashe (Midlands State University, 2017)
The signing of the Lancaster agreement in 1979 led to Land reform in Zimbabwe and to an effort to more equitably distribute land between the historically disenfranchised blacks and the minority whites who ruled Southern Rhodesia from 1890 to 1979.The distribution of land that was held by the government was the most crucial and most bitterly contested political issue surrounding Zimbabwe. The land reform can be divided into two phase’s form 1979 to 1997 where the principle of willing and buyer seller was useful with economic help from Britain and secondly beginning in 2000, the fast track land reform program. The Fast Track Land Reform Programme implemented in an accelerated manner in Zimbabwe during 2000-2002 resulted in a major and drastic reconfiguration of land use and ushered in a new regime of gender relations on land. Although much has been documented about the fast track land reform programme, the gendered outcomes of the programme, especially the consequences on different categories of women still remain an inadequately researched area. This study is a gender analysis of the land reform programme in Zimbabwe as a country that inherited colonially structured and unequal land ownership patterns. The primary purpose of the study was to make a critical evaluation of the distribution of land between men and women under the fast track land reform programme using a gender approach. The study used survey data collected by the African Institute of Agrarian Studies and qualitative data gathered in Goromonzi District. The qualitative data were collected using questionnaire interviews, focus group discussions, observations and document analysis in order to support the evidence. The study did not find evidence of the discrimination of married women. The study revealed that women enjoyed the same land rights as men in land resettlement schemes in Zimbabwe. Women were assigned land rights as individuals and through joint registration of offer letters with their husbands. The study recommended that there should be legal recognition of dual-headed households in the land redistribution programme. The allocation of land under the land reform programme should focus on individuals within households. Methods should be devised to inform women about their land rights and the avenues through which these rights can be enforced. Future research should focus on the security of women’s land rights in the event of divorce.